2014
DOI: 10.1186/2049-1891-5-36
|View full text |Cite
|
Sign up to set email alerts
|

Mammary stem cells: expansion and animal productivity

Abstract: Identification and characterization of mammary stem cells and progenitor cells from dairy animals is important in the understanding of mammogenesis, tissue turnover, lactation persistency and regenerative therapy. It has been realized by many investigators that altered lactation, long dry periods (non-milking period between two consecutive lactation cycles), abrupt cessation of lactation (common in water buffaloes) and disease conditions like mastitis, greatly reduce milk yield thus render huge financial losse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Drying-off has been widely recognized as a critical period of the production cycle of dairy cows (Capuco and Akers, 1999;Bachman and Schairer, 2003;Choudhary, 2014). It has been suggested that with increasing milk yields over the last decades, the transition from lactating to dry has progressively become more challenging for cows in terms of animal health and welfare (Thornton, 2010;Zobel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Drying-off has been widely recognized as a critical period of the production cycle of dairy cows (Capuco and Akers, 1999;Bachman and Schairer, 2003;Choudhary, 2014). It has been suggested that with increasing milk yields over the last decades, the transition from lactating to dry has progressively become more challenging for cows in terms of animal health and welfare (Thornton, 2010;Zobel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among the 96 compounds, Xanthosine showed the highest peak area (15.79%). Xanthosine was found to have wound healing, antibacterial property, and also have application in stem cell research (Choudhary, 2014). The other compounds having comparatively high peak area were naphthalene (5.39%), 9,9-Perhydrobiphenanthryl (4.75%), 4-((1e)-3-hydroxy-1propenyl)-2-methoxyphenol (4.54%), 3,6,9-triethyl-3,6,9trimethyl tetracyclo[6.1.0.0~2,4~.0~5,7~]nonane (3.12%), and the remaining showed less than 3% of peak area.…”
Section: Resultsmentioning
confidence: 99%
“…Histomorphological features of poorly differentiated MEC can be observed by visualizing cellular morphology wherein the cells are smaller in size, absence of fat vacuole inside the cytoplasm and reduced cytoplasmic area. 17,18 In mammary carcinomas, aberrant expression of MUC1 was seen. MUC1 was located in the nuclei plus cytoplasm of majority of the MEC ( Figure 4C).…”
Section: Immunolocalization Of Muc1 and Ki67mentioning
confidence: 99%